Students’ low motivation in learning English at Ngo Tri Hoa High school: Reasons and solutions = Động lực thấp trong việc học tiếng Anh của học sinh trường THPT Ngô Trí Hòa: Các nguyên nhân và các giải pháp. M.A Thesis Linguistics: 60 14 10 - Hoàng, Văn Hợi (University of Languages and International Studies, 2017)
This study was aimed at investigating factors of low motivation in learning English of the students at Ngo Tri Hoa high school in Dien Chau district, Nghe An province, the degree of influence of different de-motives on them and their suggestions overcoming (...)